Antioxidant content of parts of Mahkota dewa, Phaleria macrocarpa [Scheff] Boerl. (Thymelaceae) - ARIF SOEKSMANTO; YATRI HAPSARI; PARTOMUAN SIMANJUNTAK (Biodiversitas Journal of Biological Diversity, 2007)
Mahkota dewa (Phaleria macrocarpa [Scheff.] Boerl.) is a poisonous plant, but almost all parts of the plants can be used as a traditional medicine. Consuming the plant directly can cause swollen, sprue, numb at tongue, fever, even unconscious. Although the plant can conquere various diseases, from diabetes mellitus, hemorrhoid, impotency to cancer, but research on the plant is still limited. A researchwas conducted to find out antioxidant activities at a parts of mahkota dewa plant by free radical scavenging method (DPPH). The highest activities of the parts of plant are young fruits and old fruits in the ethanol and methanol solvents. Then after partitioned based on the polarity (ethylacetate, n-buthanol and water) showed that n-buthanol extract of young fruits gave inhibition value IC50 = 41,07 ppm.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Mahkota dewa, P. macrocarpa, plant extracts, antioxidant, DPPH